Raman spectra of InᵪTl₁₋ᵪI substitutional solid solutions - Dovhyi, Ya.O.; Ternavska, S.V.; Franiv, A.V.; Bovgyra, O.V.; Savchyn, O.V. (Functional Materials, 2005)
The structure of Raman spectra of InᵪTl₁₋ᵪI substitutional solid solutions (х = 0.2, 0.3, 0.4, 0.5, 0.7) oriented in the (а,с) plane has been studied. Basing on the group theory Analysis, the symmetry of phonon modes has been classified. The Fano anti-resonances have been revealed in the Raman spectra. The role of free carriers in the mechanism of essential changes in the phonon spectrum structure is discussed as depending on thallium content.